Our education system works internationally - Abdul Razak, Dzulkifli (Sun Media Corporation Sdn Bhd, 2019)
ON the sidelines of the Sarajevo Business Forum last week, I visited a few universities in the Bosnian capital. This “internationalisation” is now part of the mission of many universities. I have some difficulty accepting this and have for long envisaged that internationalisation was a “construct” created to serve a western-centric agenda.